Design and implementation of reconfigurable intelligent surface control circuits - Wang, Haotian (Nanyang Technological University, 2025)
Reconfigurable Intelligent Surface (RIS) is suitable for high-speed data communication. However, the RIS control circuit faces several technical challenges, such as achieving independent control of many RIS units in large-scale arrays and addressing issues related to signal integrity. Numerous studies have shown that multilayer PCB technology can optimize routing and mitigate signal integrity issues. In this work, multilayer PCB technology was initially selected for designing and implementing the RIS routing. However, due to the unique 3D structure of the RIS units, it was not feasible to employ multilayer technology during the fabrication of the 16×16 RIS array. Ultimately, single-layer PCB technology was used for the RIS routing. This study proposed two control circuit designs: one involving Arduino on an I2C bus and another using a cascading shift register approach. Both methods were validated through simulation tests and demonstrated the ability to achieve the desired functionality. From a cost perspective, the cascading shift register method was ultimately chosen for the RIS control circuit. A physical PCB was manufactured by the factory to conduct hardware testing. Experimental results demonstrate that the cascading shift register control circuit achieves independent control of each RIS unit. The code was further improved to allow real-time control of the on/off states of any number of units through command statements sent via PC serial communication. Additionally, the entire circuit was secured with polystyrene to facilitate subsequent testing. Since this design has successfully passed LED hardware tests, it is ready to find applications for 16×16 RIS array.